Turnover do carbono-13 em tecidos de frangos de corte pelo método de linearização - Russo, Jessica Conteçote [UNESP] (2014)
The present study was aimed to determine the turnover of carbon in the blood, plasma, pectoral muscle and liver in broilers, through analysis of isotopic carbon ratios, using the 13C natural variation between plants of different photosynthetic cycle. We used 150 male broilers chicks (Cobb) of one day old, casually distributed in experimental shed. All birds were fed a diet based on corn and soybean meal (predominantly C4) for the first 48 days of life and, at 49 days of age, when there was a lower rate of growth of the animals began to receive diet consisting of rice and soybean (predominantly C3). To measure quantatively the carbon rate substitution of the diets on the birds tissues (turnover), was performed linearization of the data and linear regression. The half-life found in pectoral muscle, liver, blood and plasma were, respectively: 14,4; 2,7; 12,1 and 2,9 days. For the blood has not been possible to determine the amount of pools, the muscle, liver and plasma presented two pools and the first pool was quicker shifts. The percentage contribution of the 1° and 2 ° metabolic pool were, respectively: 44 and 56 for muscle, 76 and 24 for liver and the plasma 87 and 13%. The model defined for calculating of the general half-life is viable for stable isotope data, showing higher reliability in the technique used for linearization